Rapid detection and evolutionary analysis of Legionella pneumophila serogroup 1 sequence type 47. (April 2017) - Mentasti, M.; Cassier, P.; David, S.; Ginevra, C.; Gomez-Valero, L.; Underwood, A.; Afshar, B.; Etienne, J.; Parkhill, J.; Chalker, V.; Buchrieser, C.; Harrison, T.G.; et al.
Abstract: Objectives: Legionella pneumophila serogroup 1 (Lp1) sequence type 47 is the leading cause of legionellosis in north-western Europe, but, surprisingly, it is rarely isolated from environmental samples. Comparative genomics was applied to develop a PCR assay and to better understand the evolution of this strain. Methods: Comparative analysis of 36 genomes representative of the Lp species was used to identify specific PCR targets, which were then evaluated in silico on 545 sequenced genomes and in vitro on 436 Legionella strains, 106 respiratory samples, and three environmental samples from proven ST47 sources. Phylogenetic analyses were performed to understand the evolution of ST47. Results: The gene LPO_1073 was characterized as being 100% conserved in all 129 ST47 genomes analysed. A real-time PCR designed to detect LPO_1073 was positive for all 110 ST47 strains tested and agreed with culture and typing results previously obtained for 106 respiratory samples. The three environmental samples were also positive. Surprisingly, 26 of the 44 ST109 strains tested among 342 non-ST47 strains scored positive for LPO_1073. SNP-based phylogenetic analysis was undertaken to understand this result: the PCR-positive ST109 genomes were almost identical to ST47 genomes, with the exception of a recombined region probably acquired by ST47 from a ST62(-like) strain. Conclusion: The genomic analysis allowed the design of a highly specific PCR assay for rapid detection of ST47 strains. Furthermore, it allowed us to uncover the evolution of ST47 strains from ST109 by homologous recombination with ST62. We hypothesize that this recombination generated the leading cause of legionellosis in north-western Europe.